Chronic pancreatitis and pancreatic carcinoma. Issue 863 (September 1997) - Evans, J. D.; Morton, D. G.; Neoptolemos, J. P.
Abstract : The differential diagnosis between pancreatic cancer and chronic pancreatitis is very important as the management and prognosis of these two diseases is different. In most patients with pancreatic disease, the diagnosis can be established but there is a subgroup of patients in whom it is difficult to differentiate between these conditions because the clinical presentation is often similar and currently available diagnostic tests may be unable to distinguish between an inflammatory or neoplastic pancreatic mass. This paper reviews the aetiology, pathology and clinical features of these diseases and discusses the limitations of conventional diagnostic methods and how newer techniques may be of value in the differential diagnosis.